Monitoring dan Evaluasi Kinerja Manajemen PKRS Rumah Sakit Bhayangkara Banda Aceh - Suriani, Suriani; Darusman, Darusman (NHM PRESS, 2023)
Hospitals are public services that are chosen by the community to obtain health services. To choose the type of service in the hospital, patients and their families need knowledge about the flow of services, types of services, completeness of medical personnel, facilities and infrastructure of medical devices. Health promotion in hospitals is very important in an effort to improve the quality and quantity of services for the community. The importance of monitoring and evaluating the performance of PKRS management is an illustration of the implementation of the hospital health promotion system in accordance with PKRS Technical Guidelines No. 4 of 2012 and Permenkes No. 44 of 2018. Bhayangkara Hospital formed a PKRS Team to carry out all PKRS activities both at the hospital and outside the hospital. In this study, the subject of research was the PKRS Team as the management of PKRS implementation based on the Decree of the hospital Director. The research was conducted with in-depth interviews with resource persons from Subbag. Binfung as the Chairperson of the PKRS Team and staff, document review of the Director's decree on the PKRS organizational structure, monitoring and evaluation to serve as the basis for formulating PKRS management performance evaluation. The results showed that the PKRS Bhayangkara Team consisting of 3 Kaur who handle PKRS activities together have never conducted monitoring and evaluation of PKRS management performance.